Identification of Cytomegalo Virus Infection Among Mycobacterium Tuberculosis in Baghdad City. Correlation between TB and CMV infection - Ali AL-ATTWANI; Oral DÜZDEMIR (Modern Medicine, 2024)
Objectives: Human cytomegalovirus (HCMV) infection and immunological activation are risk factors for tuberculosis disease, according to recent research. Materials and Methods: The best procedure for the detection (TB) was investigated by Ziehl Neelsen and Auramine O (AO) technology. 315 sputum samples were collected randomly. The ZN approach produced a smear positivity rate for AFB of 49/315 (15.55%) while the LED Auramine O staining method produced a positivity rate of 69/315 (21.9%), One hundred serum samples were subjected to HCV IgG and IgM detection using Cassette method and ELISA techniques. Results: The results of the cassette method documented there were 62/100 (62%) cases of M. tuberculosis patients who had HCMV IgG versus 16/100 (16%) cases who had HCMV having IgM (P-value= 0.001). While the results of ELISA techniques observed there were 65 (65%) cases of M. tuberculosis patients had HCMV IgG versus 17/100 (17%) cases had HCMV had IgM these differences statistically were highly significant. These results observed the sensitivity of the cassette method and ELISA procedure for diagnosis of CMV among M.tuberculosis were 92% for IgG and 94% for IgM antibodies. Conclusions: According to recent findings from CMV infection significantly increases the probability of active TB disease.